Message Security in Classical Cryptography Using the Vigenere Cipher Method - Purwanti; Nurcahya , Saputra Dwi; Nazelliana, Dian (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Ensuring message confidentiality is a fundamental aspect of classical cryptography. This study uses the Vigenere Cipher, a prominent polyalphabetic substitution technique, to secure alphabetic text. The historical development of the Vigenere Cipher, introduced by Blaise de Vigenère, marked a significant advancement in cryptographic practices by offering enhanced security over monoalphabetic ciphers. The method's ability to obscure letter frequency analysis made it a robust choice for protecting sensitive information. However, the Vigenere Cipher has vulnerabilities, particularly in brute force attacks when short keys are used. This research explores the technical specifications, strengths, and limitations of the Vigenere Cipher, comparing it with other classical and modern cryptographic algorithms. Additionally, potential enhancements and practical applications of the Vigenere Cipher in contemporary data security contexts are discussed, emphasizing the need for ongoing innovation and adaptation in cryptographic methods to address evolving security challenges.